The use of chestnuts (Castanea sativa Mill.) as a source of resistant starch in the diet of the weaned piglet - Ribeiro, R.S. (2013)
tTwenty-four piglets, with a mean weight of 6.11 kg, were allocated to three experimentaldiets (8 piglets per diet). The starch content of the experimental diets was 39% consistingeither of 100% wheat starch (CD), 50% wheat starch and 50% chestnut starch (CN50) or 100%chestnut starch (CN100). The piglets received these diets for 35 days. Total tract apparentdigestibility (TTAD) was measured when piglets were aged 32–39 days and 46–53 days.Afterwards, the animals were sacrificed, their gastrointestinal compartments weighed, andthe contents of their caecum and colon collected. Diet did not influence the feed intakeor growth rate of the piglets, but had a significant effect on their feed conversion ratiowhich was 1.27, 1.30 and 1.37 for diets CD, CN50 and CN100, respectively (P=0.042). Pigletsreceiving the CN50 diet exhibited lower faecal scores compared to CD and CN100 groups( 2= 39.31, P<0.001). There was a trend (P=0.067) towards an increase in the TTAD of drymatter (DM) in the two chestnut-containing diets, but only when piglets were younger(32–39 days). The TTAD of crude protein (CP) was decreased (P<0.001) in CN100 group rel-ative to CD and CN50 groups, independently of age. Relative to the CD group, the coefficientof TTAD of NDF was increased by 0.18 units in the CN50 group and 0.25 units in the CN100group, when the piglets were aged 32–39 days. These differences were reduced to 0.09 and0.17 units, respectively, when the piglets were aged 46–53 days. There were tendencies(P<0.10) towards increases in the full and empty weights of the large intestine in CN100group. Moreover, diet had no significant effect on villus height and width. In the jejunum,crypt depth was reduced in CN100 group (P=0.006), while the villus height:crypt depth ratiowas increased with the CN50 and CN100 diets (P=0.018). Diet had no significant effect onDM and pH of the caecal or colonic contents. In the caecum, the concentration (mmol l−1) ofpropionic acid was 5.15, 9.43 and 14.7 (P=0.042) for diets CD, CN50 and CN100, respectively.The concentration (mmol l−1) of butyric acid was 3.50, 4.90 and 9.84 (P=0.025). Conversely,diet had no significant effect on the concentration of short chain fatty acids in the colon.In conclusion, chestnuts could be used as an alternative source of RS in the diet of weanedpiglets, although their feed conversion ratio (FCR) may be worsened